1975
DOI: 10.1161/01.res.36.6.57
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II and potassium in the long-term regulation of aldosterone secretion in intact conscious dogs.

Abstract: The aldosterone response to long-term infusion of angiotensin II and potassium was studied in intact conscious dogs. Plasma aldosterone concentration (PAC), plasma renin activity (PRA), and plasma cortisol concentration (PCC) were determined by radioimmunoassay. In ten dogs maintained on angiotension II infusion (5 ng/kg min-1) for 14 days, PAC increased from 6.9 plus or minus 2.9 to 18.6 plus or minus 4.7 ng/100 ml plasma (mean plus or minus SE) within ten minutes after beginning the infusion, reached a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…fore surgery, extremely high aldosterone levels were maintained by angiotensin II despite the inhibitory effects of mild hypokalemia (3.3 mmol/liter in Patient HE, 3.1 mmol/liter in Patient MC). While there is still controversy concerning the effect of sustained increases in angiotensin II on aldosterone, 22 " 24 the present findings support those of the Glasgow group 25 who showed similar angiotensin/aldosterone relationships in a mixed group of patients with malignant hypertension, renin-secreting tumor, and renal artery stenosis. We conclude, first, that long-standing elevations in angiotensin II secondary to renal ischemia can sustain high circulating levels of aldosterone; and, second, that aldosterone responsiveness to endogenous angiotensin II stimulation is increased in established renovascular hypertension.…”
Section: -supporting
confidence: 82%
“…fore surgery, extremely high aldosterone levels were maintained by angiotensin II despite the inhibitory effects of mild hypokalemia (3.3 mmol/liter in Patient HE, 3.1 mmol/liter in Patient MC). While there is still controversy concerning the effect of sustained increases in angiotensin II on aldosterone, 22 " 24 the present findings support those of the Glasgow group 25 who showed similar angiotensin/aldosterone relationships in a mixed group of patients with malignant hypertension, renin-secreting tumor, and renal artery stenosis. We conclude, first, that long-standing elevations in angiotensin II secondary to renal ischemia can sustain high circulating levels of aldosterone; and, second, that aldosterone responsiveness to endogenous angiotensin II stimulation is increased in established renovascular hypertension.…”
Section: -supporting
confidence: 82%
“…The hypertension seems to be more a function of the peripheral vasoconstrictor effects of A II and the renal effects of A II which promote sodium retention. 12 ' 18 In contrast to the data reported by McCaa et al, 11 in the present study, chronic infusion of A II VOL. 43, No.…”
contrasting
confidence: 70%
“…Finally, although circumstantial to the present study, prolonged infusions of A II under different experimental conditions might provide further insight into the role of the renin-angiotensin system in the long-term control of aldosterone secretion, particularly since it has been reported that chronic infusion of A II fails to produce a sustained increase in plasma aldosterone concentration in sodium-replete dogs. 11 Therefore, to generate quantitative data relating to the effects of excess aldosterone on arterial pressure, we infused aldosterone chronically into both adrenalectomized and intact dogs. Also, high levels of aldosterone were administered both in normal dogs and in dogs receiving A II given to suppress PRA and thus prevent changes in plasma levels of A II during the aldosterone infusion.…”
mentioning
confidence: 99%
“…The present observations have extended the analysis of angiotensin's role in sodium deficiency by blocking formation of the peptide in sodium-deprived rats. Infusion of the converting enzyme inhibitor can lead to increased plasma bradykinin levels, as well as the anticipated decrease in angiotensin II formation (33). However, no effects of bradykinin upon angiotensin-stimulated aldosterone production have been detected in isolated adrenal glomerulosa cells (unpublished observations) and there is no reason to believe that actions of bradykinin are involved in the present study.…”
Section: Discussionmentioning
confidence: 54%